Who Has Terror Angst? Perceptions of the Effects of Terror on the World Economy - Dorine Boumans; Johanna Garnitz; Günther G. Schulze (Center for Economic Studies and ifo Institute (CESifo), 2016)
We examine sources of biased terror perceptions. In particular, we investigate how international experts of the IFO World Economic Survey assess the effect of terror on the world economy and the economy of their own country. The results show that respondents from terror stricken countries have more favorable views on the effect of terror on the word economy (but not on their own countries). Male respondents and those from democratic and richer countries are likewise more optimistic.
Keywords: D74; D84; F01; 330; terror; terror angst; terror perceptions; consequences of terror